The dynamic of human EEG alpha-activity in the loop of brain — computer interface during trigger photo stimulation - A. Ya. Kaplan; A. Yu. Zhigalov (Бюллетень сибирской медицины)
Trigger photo stimulation (TPS), based on synchronization of flashes of light with events in a brain, for example, with waves of alpha activity EEG, is widely known as a methodical approach for studying of mechanisms of a brain and also as a method of neurologic diagnostics. In the present work TPS has been used for the first time as an element of the brain — computer interface (BCI) where the start of light flashes determined by crossing of definite level by amplitude of EEG alpha-waves. It has been shown that specific reorganizations of alpha-waves time distribution during BCI-training. It testifies that brain develops a new control path by means of EEG alpha-patterns.